Differences in characteristics of error-related potentials between individuals with spinal cord injury and age- and sex-matched able-bodied controls - Keyl, Philipp; Schneiders, Matthias; Schuld, Christian; Franz, Steffen; Hommelsen, Maximilian; Weidner, Norbert; Rupp, Rüdiger (Frontiers in neurology, 2019)
Background: Noninvasive brain-computer interfaces (BCI) represent an emerging technology for enabling persons with high spinal cord injury (SCI) and the associated loss of grasping and reaching function to control assistive devices. A major drawback of BCIs is a high rate of wrong classifications. The robustness and performance of BCIs might be improved using cerebral electrophysiological correlates of error recognition (error-related potentials, ErrPs). As ErrPs have never been examined in subjects with SCI, this study compares the characteristics of ErrPs in individuals with SCI with those of able-bodied control subjects. Methods: ErrPs at FCz and Cz were analysed in 11 subjects with SCI (9 male, median age 28 y) and in 11 sex- and age-matched controls. Moving a shoulder joystick according to a visual cue, subjects received feedback about the match/mismatch of the performed movement. ErrPs occurring after “error”-feedback were evaluated by comparing means of voltage values within three consecutive time windows after feedback (wP1, wN1, wP2 containing peak voltages P1, N1, P2) using repeated-measurement analysis of variance. Results: In the control group, mean voltage values for the “error” and “correct” feedback condition differed significantly around N1 (FCz: 254 ms, Cz: 252 ms) and P2 (FCz: 347 ms, Cz: 345 ms), but not around P1 (FCz: 181 ms, Cz: 179 ms). ErrPs of the control and the SCI group showed similar morphology, however mean amplitudes of ErrPs were significantly smaller in individuals with SCI compared to controls for wN1 (FCz: control = -1.55 µV, SCI= -0.27 µV, p = 0.02; Cz: control = -1.03 µV, SCI = 0.11 µV, p = 0.04) and wP2 (FCz: control = 2.79 µV, SCI = 1.29 µV, p=0,011; Cz: control = 2.12 µV, SCI = 0.81 µV, p = 0.003)). Mean voltage values wP1, wN1 and wP2 did not correlate significantly with either chronicity after or level of injury. Conclusion: The morphology of ErrPs in subjects with and without SCI is comparable, however, with reduced mean amplitude in wN1 and wP2 in the SCI group. Further studies should therefore evaluate whether ErrP-classification can be used for online correction of false BCI-commands in individuals with SCI.